Acceptance of Public Health Measures During the COVID-19 Pandemic: A Cross-Sectional Study of the Swiss Population’s Beliefs, Attitudes, Trust, and Information-Seeking Behavior - Maddalena Fiordelli; Maddalena Fiordelli; Sara Rubinelli; Sara Rubinelli; Nicola Diviani; Nicola Diviani (International Journal of Public Health, 2023)
Objectives: This study aimed to advance the understanding of the factors associated with population acceptance of public health measures during the COVID-19 pandemic.Methods: In January 2022, we conducted a cross-sectional survey of the Swiss population (N = 2,587). Questionnaires were administered through computer-assisted web interviewing. Measures covered included information-seeking behavior, attitudes towards and beliefs about public health measures enacted, and trust in institutions.Results: Television and newspapers were the most used information sources. Those with higher education levels were more likely to use channels from public institutions, newspapers, and television. The most important criterion for reliable information was scientific evidence. Trust was highest for doctors, healthcare workers, universities, research institutes, and public health institutions. Acceptance of public health measures was high overall, and attitudes, beliefs, information-seeking behavior, and trust were positively related to acceptance. Trust in science remained stable, while trust in public health institutions decreased slightly.Conclusion: While nurturing a two-way dialogue with the population, institutions should target communication considering age and culture, improve risk communication, ground messages in scientific evidence, and ensure mass media presence.